The effects of 6 weeks eccentric training on speed, dynamic balance, muscle strength, power, and lower limb asymmetry in prepubescent weightlifters - Hammami, R.; Duncan, M. J.; Nebigh, A.; Werfelli, H.; Rebai, H. (The Journal of Strength and Conditioning Research, 2022)
This study examined whether 6 weeks of twice-weekly in-season hamstring eccentric training would enhance selected performance-related abilities in prepubescent male weightlifters. Twenty elite weightlifters (11.1 ± 0.8 years) were randomly split into an eccentric training intervention group (INT n = 10) or a control group (CON) that maintained their standard in-season regimen (n = 10). Pre-intervention and postintervention speed, dynamic balance, muscle strength, power, and lower limb (LL) asymmetry were assessed. Analysis of covariance controlling for maturation was used to determine any differences in the performance variables. There were no significant changes in muscle strength, dynamic balance, or LL asymmetry (all p < 0.05) because of the intervention. Both 10-m (p = 0.001) and 30-m (p = 0.007) sprint speed and agility (p = 0.049) improved to a greater extent in INT compared with the CON group. Similar results were evident for the standing long jump (p = 0.015) and 3 hop test (p = 0.004) where performance improved to a greater magnitude in INT compared with CON groups. This study suggests that eccentric training, undertaken twice weekly for 6-weeks results in positive changes in sprint speed, change of direction speed, and power performance, but not muscle strength, dynamic balance, or LL asymmetry in prepubertal weightlifters.